Ion-transport study in nanocomposite solid polymer electrolytes based on chitosan: electrical and dielectric analysis - Aziz, Shujahadeen B.; Abidin, Zul Hazrin Zainal (Wiley, 2015)
In this study, (1.1111 - x)(0.9CS-0.1NaTf)-xAl(2)O(3)(0.02 <= x <= 0.1) [where CS is chitosan, NaTf is sodium triflate (NaCF3SO3), and Al2O3 is aluminum oxide] nanocomposite solid polymer electrolyte (SPE) films based on CS were prepared by a solution casting technique. X-ray diffraction and scanning electron microscopy analysis revealed that the alumina nanoparticles had a great effect on the structural and morphological behavior of the CS-NaTf (90:10) polymer electrolyte. An investigation of the electrical and dielectric parameters of the nanocomposite SPE films was conducted. Electrical impedance spectroscopy was carried out for this purpose. The relationships between the electrical and dielectric parameters were used to interpret and understand the ion-conduction mechanism. We observed that the direct-current conductivity (sigma(dc)) and dielectric constant followed the same trend with salt concentration. sigma(dc) versus temperature showed the Arrhenius and Vogel-Fulcher-Tammann (VTF) regions. The drops of sigma(dc) at high temperatures were observed for all of the samples. The ion relaxation dynamics were studied from Argand plots. For the first time, we confirmed the existence of a strong experimental relationship between the high-frequency semicircle of the impedance plots and the high-frequency dispersion regions of the alternating-current conductivity (sigma(ac)). The dispersion regions of sigma(ac) were used to study the ion-conduction mechanism. The behavior of the frequency exponent as a function of the temperature was used to interpret sigma(dc) versus the temperature. (C) 2014 Wiley Periodicals, Inc.